Methodological and practical insights from Australian research on urban climate change impacts and adaptation - Dovers, Stephen; Geraldine Li (Environmental Management Society, Malaysia, 2009)
Cities and towns will house the majority of the world’s population in future, and these human habitats will be impacted upon by predicted climate change. In the last two years, attention has shifted from (i) whether climate change will happen and to what extent, toward what societies’ responses should be, and (ii) from a largely natural science-led debate to one where social science and professional and community knowledge are called upon. As coarser scale scenarios generated from climate models have become more accepted, there is now increasing focus on understanding climate change at finer scales to inform responses at the local and municipal level which is where many policy and management decisions are made. This paper presents insights for climate change impact assessment methodologies and practical adaptive responses for smallmedium scale urban settlements, drawing on an integrated assessment (IA) of five Australian settlements. The paper outlines the IA methodology developed – Integrated Systems Risk and Vulnerability Assessment – how selected climate impacts were investigated, and summarises insights into the practice of local scale assessment and adaptation